Analysis and Design of a Novel Dual-Trap LCL Inverter Output Filter for HS-PMSM Drives - Zhenxing Cheng; Liyi Li; Le Pei; Jiwei Cao; Jiaxi Liu (IEEE Access, 2024)
High-speed permanent magnet synchronous motors face significant stator current harmonics issues due to small stator inductance and low carrier ratio. LCL topology family of filters are unable to ensure optimal filtering performance across the full frequency domain. This paper proposes a novel high-order dual-trap filter for high-speed permanent magnet synchronous motor (HS-PMSM) to enhance the filtering performance. The proposed filter utilizes the stator inductance to construct the LCL-based topology, enabling high attenuation of harmonics in the high-frequency range, and trap branches achieve strong suppression of harmonics near the switching frequency and its multiples. Furthermore, the filter improves robustness in response to parameter variations by tuning parameters of trap branches. The paper improves the filter parameter design guidelines by considering the specific characteristics of HS-PMSM. Additionally, a PI control parameter design methodology is presented, utilizing the amplitude margin and phase margin of the open-loop transfer function. The effectiveness and feasibility of the proposed method is validated through comprehensive experimental analyses, comparing the performance of traditional filters against the proposed filter.